Molecular-scale synchrotron X-ray investigations of solid-liquid interfaces in lithium-ion batteries - Cao, Chuntian; Steinrück, Hans-Georg (Reference Module in Chemistry, Molecular Sciences and Chemical Engineering)

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Creating water-in-salt-like environment using coordinating anions in non-concentrated aqueous electrolytes for efficient Zn batteries - Gomez Vazquez, Dario; Pollard, Travis P.; Mars, Julian; Yoo, Ji Mun; Steinrück, Hans-Georg; Bone, Sharon E.; Safonova, Olga V.; Toney, Michael F.; Borodin, Oleg; Lukatskaya, Maria R. (Energy & Environmental Science)
By using coordinating anions such as acetate, a water-in-salt-like coordination environment of Zn ions is achieved in relatively dilute conditions, leading to prolonged and efficient cycling of zinc metal anodes.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

The nature of dynamic local order in CH3NH3PbI3 and CH3NH3PbBr3 - Weadock, Nicholas J.; Sterling, Tyler C.; Vigil, Julian A.; Gold-Parker, Aryeh; Smith, Ian C.; Ahammed, Ballal; Krogstad, Matthew J.; Ye, Feng; Voneshen, David; Gehring, Peter M.; Rappe, Andrew M.; Steinrück, Hans-Georg; et al. (Joule)
Keywords: General Energy

X-ray Absorption Spectroscopy Reveals Mechanisms of Calcium and Silicon Fouling on Reverse Osmosis Membranes Used in Wastewater Reclamation - Niemann, Valerie A.; Huck, Marten; Steinrück, Hans-Georg; Toney, Michael F.; Tarpeh, William A.; Bone, Sharon E. (ACS ES&T Water)
Keywords: Water Science and Technology; Environmental Chemistry; Chemistry (miscellaneous); Chemical Engineering (miscellaneous)

Molecular Adhesion of a Pilus‐derived Peptide Involved in Pseudomonas aeruginosa Biofilm Formation on non‐polar ZnO Surfaces - Prüßner, Tim; Meinderink, Dennis; Zhu, Siqi; Orive, Alejandro G.; Kielar, Charlotte; Huck, Marten; Steinrück, Hans-Georg; Keller, Adrian; Grundmeier, Guido (Chemistry – A European Journal)
Bacterial colonization and biofilm formation on abiotic surfaces are initiated by the adhesion of peptides and proteins. Understanding the adhesion of such peptides and proteins at a molecular level thus represents an important step toward controlling and suppressing biofilm formation on technological and medical materials. This study investigates the molecular adhesion of a pilus‐derived peptide that facilitates biofilm formation of Pseudomonas aeruginosa, a multidrug‐resistant opportunistic pathogen frequently encountered in healthcare settings. Single‐molecule force spectroscopy (SMFS) was performed on chemically etched ZnO surfaces to gather insights about peptide adsorption force and its kinetics. Metal‐free click chemistry for the fabrication of peptide‐terminated SMFS cantilevers was performed on amine‐terminated gold cantilevers and verified by X‐ray photoelectron spectroscopy (XPS) and polarization‐modulated infrared reflection absorption spectroscopy (PM‐IRRAS). Atomic force microscopy (AFM) and XPS analyses reveal stable topographies and surface chemistries of the substrates that are not affected by SMFS. Rupture events described by the worm‐like chain model (WLC) up to 600 pN were detected for the non‐polar ZnO(11‐20) surfaces. The dissociation barrier energy at zero force ΔG(0), the transition state distance xb and bound‐unbound dissociation rate at zero force koff(0) for the single crystalline substrate indicate that coordination and hydrogen bonds dominate the peptide/surface interaction.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Heterogeneous Structural Evolution of In–Zn–O Thin Films during Annealing - Moffitt, Stephanie L.; Cao, Chuntian; Van Hest, Maikel F. A. M.; Schelhas, Laura T.; Steinrück, Hans-Georg; Toney, Michael F. (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Ammonium enables reversible aqueous Zn battery chemistries by tailoring the interphase - Ma, Lin; Pollard, Travis P.; Zhang, Yong; Schroeder, Marshall A.; Ren, Xiaoming; Han, Kee Sung; Ding, Michael S.; Cresce, Arthur V.; Atwater, Terrill B.; Mars, Julian; Cao, Longsheng; Steinrück, Hans-Georg; et al. (One Earth)
Keywords: Earth and Planetary Sciences (miscellaneous); General Environmental Science

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Simultaneous neutron and X-ray tomography for visualization of graphite electrode degradation in fast-charged lithium-ion batteries - Yusuf, Maha; LaManna, Jacob M.; Paul, Partha P.; Agyeman-Budu, David N.; Cao, Chuntian; Dunlop, Alison R.; Jansen, Andrew N.; Polzin, Bryant J.; Trask, Stephen E.; Tanim, Tanvir R.; Dufek, Eric J.; Thampy, Vivek; et al. (Cell Reports Physical Science)
Keywords: General Physics and Astronomy; General Energy; General Engineering; General Materials Science; General Chemistry

Combined Effects of Uniform Applied Pressure and Electrolyte Additives in Lithium-Metal Batteries - Kasse, Robert M.; Geise, Natalie R.; Sebti, Elias; Lim, Kipil; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Toney, Michael F. (ACS Applied Energy Materials)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Electrochemistry; Energy Engineering and Power Technology; Chemical Engineering (miscellaneous)

Giant Orbital Anisotropy with Strong Spin–Orbit Coupling Established at the Pseudomorphic Interface of the Co/Pd Superlattice - Kim, Sanghoon; Pathak, Sachin; Rhim, Sonny H.; Cha, Jongin; Jekal, Soyoung; Hong, Soon Cheol; Lee, Hyun Hwi; Park, Sung‐Hun; Lee, Han‐Koo; Park, Jae‐Hoon; Lee, Soogil; Steinrück, Hans-Georg; et al. (Advanced Science)
Keywords: General Physics and Astronomy; General Engineering; Biochemistry; Genetics and Molecular Biology (miscellaneous); General Materials Science; General Chemical Engineering; Medicine (miscellaneous)

Electrochemical performance of KTiOAsO_4 (KTA) in potassium-ion batteries from density-functional theory - Bocchini, Adriana; Gerstmann, Uwe; Bartley, Tim; Steinrück, Hans-Georg; Henkel, Gerald; Schmidt, Wolf Gero (Phys. Rev. Materials)

A mechanistic study of the dopant-induced breakdown in halide perovskites using solid state energy storage devices - Mathieson, Angus G. M.; Dose, Wesley M.; Steinrück, Hans-Georg; Takacs, Christopher J.; Feldmann, Sascha; Pandya, Raj; Merryweather, Alice J.; Mackanic, David; Rao, Akshay; Deschler, Felix; De Volder, Michael (Energy & Environmental Science)
Elucidating and quantifying the effects of doping on halide perovskites using lithium ion batteries.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Water or Anion? Uncovering the Zn2+ Solvation Environment in Mixed Zn(TFSI)2 and LiTFSI Water-in-Salt Electrolytes - Zhang, Yong; Wan, Gang; Lewis, Nicholas H. C.; Mars, Julian; Bone, Sharon E.; Steinrück, Hans-Georg; Lukatskaya, Maria R.; Weadock, Nicholas J.; Bajdich, Michal; Borodin, Oleg; Tokmakoff, Andrei; Toney, Michael F.; et al. (ACS Energy Letters)

Quantification of Efficiency in Lithium Metal Negative Electrodes via Operando X-ray Diffraction - Geise, Natalie R.; Kasse, Robert M.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Chemistry of Materials)

Toward Unraveling the Origin of Lithium Fluoride in the Solid Electrolyte Interphase - Cao, Chuntian; Pollard, Travis P.; Borodin, Oleg; Mars, Julian E.; Tsao, Yuchi; Lukatskaya, Maria R.; Kasse, Robert M.; Schroeder, Marshall A.; Xu, Kang; Toney, Michael F.; Steinrück, Hans-Georg (Chemistry of Materials)

General relationship between salt concentration and x-ray absorption for binary electrolytes - Steinrück, Hans-Georg (AIP Advances)

Using In Situ High-Energy X-ray Diffraction to Quantify Electrode Behavior of Li-Ion Batteries from Extreme Fast Charging - Paul, Partha P.; Cao, Chuntian; Thampy, Vivek; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew N.; Dufek, Eric J.; Nelson Weker, Johanna; Toney, Michael F. (ACS Applied Energy Materials)

Unraveling the Unconventional Order of a High-Mobility Indacenodithiophene–Benzothiadiazole Copolymer - Cendra, Camila; Balhorn, Luke; Zhang, Weimin; O’Hara, Kathryn; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Liang, Mengning; Toney, Michael F.; McCulloch, Iain; Chabinyc, Michael L.; Salleo, Alberto; et al. (ACS Macro Letters)

Visualization of dynamic polaronic strain fields in hybrid lead halide perovskites - Guzelturk, Burak; Winkler, Thomas; Van de Goor, Tim W. J.; Smith, Matthew D.; Bourelle, Sean A.; Feldmann, Sascha; Trigo, Mariano; Teitelbaum, Samuel W.; Steinrück, Hans-Georg; de la Pena, Gilberto A.; Alonso-Mori, Roberto; Zhu, Diling; et al. (Nature Materials)

A Review of Existing and Emerging Methods for Lithium Detection and Characterization in Li‐Ion and Li‐Metal Batteries - Paul, Partha P.; McShane, Eric J.; Colclasure, Andrew M.; Balsara, Nitash; Brown, David E.; Cao, Chuntian; Chen, Bor‐Rong; Chinnam, Parameswara R.; Cui, Yi; Dufek, Eric J.; Finegan, Donal P.; Gillard, Samuel; et al. (Advanced Energy Materials)

Modeling cyclic voltammetry during solid electrolyte interphase formation: Baseline scenario of a dynamically evolving tunneling barrier resulting from a homogeneous single-phase insulating film - Steinrück, Hans-Georg (The Journal of Chemical Physics)

Water-in-Salt LiTFSI Aqueous Electrolytes. 1. Liquid Structure from Combined Molecular Dynamics Simulation and Experimental Studies - Zhang, Yong; Lewis, Nicholas H. C.; Mars, Julian; Wan, Gang; Weadock, Nicholas J.; Takacs, Christopher J.; Lukatskaya, Maria R.; Steinrück, Hans-Georg; Toney, Michael F.; Tokmakoff, Andrei; Maginn, Edward J. (The Journal of Physical Chemistry B)

Oligothiophene Phosphonic Acids for Self-Assembled Monolayer Field-Effect Transistors - Zhao, Baolin; Gothe, Bastian; Groh, Arthur; Schmaltz, Thomas; Will, Johannes; Steinrück, Hans-Georg; Unruh, Tobias; Mecking, Stefan; Halik, Marcus (ACS Applied Materials & Interfaces)

Lamellar carbon-aluminosilicate nanocomposites with macroscopic orientation - Paripović, Dragana; Hartmann, Lucia; Steinrück, Hans-Georg; Magerl, Andreas; Li-Destri, Giovanni; Fontana, Yannik; Fontcuberta i Morral, Anna; Oveisi, Emad; Bomal, Enzo; Frauenrath, Holger (Nanoscale)
A liquid-crystalline hexaphenylene amphiphile and an aluminosilicate precursor were co-assembled and pyrolyzed to form carbon-aluminosilicate nanocomposites with controlled lamellar orientation and macroscopic order.

Quantification of heterogeneous, irreversible lithium plating in extreme fast charging of lithium-ion batteries - Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Tanim, Tanvir R.; Dunlop, Alison R.; Dufek, Eric J.; Trask, Stephen E.; Jansen, Andrew N.; Toney, Michael F.; Nelson Weker, Johanna (Energy & Environmental Science)
Realization of extreme fast charging (XFC, ≤15 minutes) of lithium-ion batteries is imperative for the widespread adoption of electric vehicles.

Orientation-Dependent Distortion of Lamellae in a Block Copolymer Electrolyte under DC Polarization - Galluzzo, Michael D.; Grundy, Lorena S.; Takacs, Christopher J.; Cao, Chuntian; Steinrück, Hans-Georg; Fu, Sean; Rivas Valadez, Michael A.; Toney, Michael F.; Balsara, Nitash P. (Macromolecules)

GIWAXS-SIIRkit: scattering intensity, indexing and refraction calculation toolkit for grazing-incidence wide-angle X-ray scattering of organic materials - Savikhin, Victoria; Steinrück, Hans-Georg; Liang, Ru-Ze; Collins, Brian A.; Oosterhout, Stefan D.; Beaujuge, Pierre M.; Toney, Michael F. (Journal of Applied Crystallography)
Grazing-incidence wide-angle X-ray scattering (GIWAXS) has become an increasingly popular technique for quantitative structural characterization and comparison of thin films. For this purpose, accurate intensity normalization and peak position determination are crucial. At present, few tools exist to estimate the uncertainties of these measurements. Here, a simulation package is introduced called GIWAXS-SIIRkit , where SIIR stands for scattering intensity, indexing and refraction. The package contains several tools that are freely available for download and can be executed in MATLAB. The package includes three functionalities: estimation of the relative scattering intensity and the corresponding uncertainty based on experimental setup and sample dimensions; extraction and indexing of peak positions to approximate the crystal structure of organic materials starting from calibrated GIWAXS patterns; and analysis of the effects of refraction on peak positions. Each tool is based on a graphical user interface and designed to have a short learning curve. A user guide is provided with detailed usage instruction, tips for adding functionality and customization, and exemplary files.

Crystallization and Organic Field‐Effect Transistor Performance of a Hydrogen‐Bonded Quaterthiophene - Gebers, Jan; Özen, Bilal; Hartmann, Lucia; Schaer, Michel; Suàrez, Stéphane; Bugnon, Philippe; Scopelliti, Rosario; Steinrück, Hans-Georg; Konovalov, Oleg; Magerl, Andreas; Brinkmann, Martin; Petraglia, Riccardo; et al. (Chemistry – A European Journal)

Impact of Processing on Structural and Compositional Evolution in Mixed Metal Halide Perovskites during Film Formation - Abdelsamie, Maged; Xu, Junwei; Bruening, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; Toney, Michael F. (Advanced Functional Materials)

Heterogeneous Behavior of Lithium Plating during Extreme Fast Charging - Tanim, Tanvir R.; Paul, Partha P.; Thampy, Vivek; Cao, Chuntian; Steinrück, Hans-Georg; Nelson Weker, Johanna; Toney, Michael F.; Dufek, Eric J.; Evans, Michael C.; Jansen, Andrew N.; Polzin, Bryant J.; Dunlop, Alison R.; et al. (Cell Reports Physical Science)

Advanced Characterization in Clean Water Technologies - Bone, Sharon E.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Understanding additive controlled lithium morphology in lithium metal batteries - Kasse, Robert M.; Geise, Natalie R.; Ko, Jesse S.; Nelson Weker, Johanna; Steinrück, Hans-Georg; Toney, Michael F. (Journal of Materials Chemistry A)
Investigation of the mechanisms underlying control of electrodeposited lithium metal morphology using electrolyte additives in lithium metal batteries.

Time‐Resolved Structural Kinetics of an Organic Mixed Ionic–Electronic Conductor - Paulsen, Bryan D.; Wu, Ruiheng; Takacs, Christopher J.; Steinrück, Hans-Georg; Strzalka, Joseph; Zhang, Qingteng; Toney, Michael F.; Rivnay, Jonathan (Advanced Materials)

Interfacial Speciation Determines Interfacial Chemistry: X‐ray‐Induced Lithium Fluoride Formation from Water‐in‐salt Electrolytes on Solid Surfaces - Steinrück, Hans-Georg; Cao, Chuntian; Lukatskaya, Maria R.; Takacs, Christopher J.; Wan, Gang; Mackanic, David G.; Tsao, Yuchi; Zhao, Jingbo; Helms, Brett A.; Xu, Kang; Borodin, Oleg; Wishart, James F.; et al. (Angewandte Chemie International Edition)

Concentration and velocity profiles in a polymeric lithium-ion battery electrolyte - Steinrück, Hans-Georg; Takacs, Christopher J.; Kim, Hong-Keun; Mackanic, David G.; Holladay, Benjamin; Cao, Chuntian; Narayanan, Suresh; Dufresne, Eric M.; Chushkin, Yuriy; Ruta, Beatrice; Zontone, Federico; Will, Johannes; et al. (Energy & Environmental Science)
Direct measurements of concentration and velocity profiles in a polymeric lithium-ion battery electrolyte provide insights into the transference number.

Interface between Water–Solvent Mixtures and a Hydrophobic Surface - Prihoda, Annemarie; Will, Johannes; Duchstein, Patrick; Becit, Bahanur; Lossin, Felix; Schindler, Torben; Berlinghof, Marvin; Steinrück, Hans-Georg; Bertram, Florian; Zahn, Dirk; Unruh, Tobias (Langmuir)

Tortuosity Effects in Lithium-Metal Host Anodes - Chen, Hao; Pei, Allen; Wan, Jiayu; Lin, Dingchang; Vilá, Rafael; Wang, Hongxia; Mackanic, David; Steinrück, Hans-Georg; Huang, William; Li, Yuzhang; Yang, Ankun; Xie, Jin; et al. (Joule)

Toward quantifying capacity losses due to solid electrolyte interphase evolution in silicon thin film batteries - Steinrück, Hans-Georg; Cao, Chuntian; Veith, Gabriel M.; Toney, Michael F. (The Journal of Chemical Physics)

Structural Origins of Light-Induced Phase Segregation in Organic-Inorganic Halide Perovskite Photovoltaic Materials - Beal, Rachel E.; Hagström, Nanna Zhou; Barrier, Julien; Gold-Parker, Aryeh; Prasanna, Rohit; Bush, Kevin A.; Passarello, Donata; Schelhas, Laura T.; Brüning, Karsten; Tassone, Christopher J.; Steinrück, Hans-Georg; McGehee, Michael D.; et al. (Matter)

Shedding X-ray Light on the Interfacial Electrochemistry of Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Shyam, Badri; Wang, Jiajun; Toney, Michael F.; Steinrück, Hans-Georg (Accounts of Chemical Research)

Morphology of Organic Semiconductors Electrically Doped from Solution Using Phosphomolybdic Acid - Huang, Tzu-Yen; Larrain, Felipe A.; Borca, Carlos H.; Fuentes-Hernandez, Canek; Yan, Hongping; Schneider, Sebastian Alexander; Chou, Wen-Fang; Rodriguez-Toro, Victor A.; Steinrück, Hans-Georg; Cao, Chuntian; Sherrill, C. David; Kippelen, Bernard; et al. (Chemistry of Materials)

Solid Electrolyte Interphase on Native Oxide-Terminated Silicon Anodes for Li-Ion Batteries - Cao, Chuntian; Abate, Iwnetim Iwnetu; Sivonxay, Eric; Shyam, Badri; Jia, Chunjing; Moritz, Brian; Devereaux, Thomas P.; Persson, Kristin A.; Steinrück, Hans-Georg; Toney, Michael F. (Joule)

Novel ALD Chemistry Enabled Low-Temperature Synthesis of Lithium Fluoride Coatings for Durable Lithium Anodes - Chen, Lin; Chen, Kan-Sheng; Chen, Xinjie; Ramirez, Giovanni; Huang, Zhennan; Geise, Natalie R.; Steinrück, Hans-Georg; Fisher, Brandon L.; Shahbazian-Yassar, Reza; Toney, Michael F.; Hersam, Mark C.; Elam, Jeffrey W. (ACS Applied Materials & Interfaces)

Fluoroethylene Carbonate Induces Ordered Electrolyte Interface on Silicon and Sapphire Surfaces as Revealed by Sum Frequency Generation Vibrational Spectroscopy and X-ray Reflectivity - Horowitz, Yonatan; Steinrück, Hans-Georg; Han, Hui-Ling; Cao, Chuntian; Abate, Iwnetim Iwnetu; Tsao, Yuchi; Toney, Michael F.; Somorjai, Gabor A. (Nano Letters)

The nanoscale structure of the electrolyte–metal oxide interface - Steinrück, Hans-Georg; Cao, Chuntian; Tsao, Yuchi; Takacs, Christopher J.; Konovalov, Oleg; Vatamanu, Jenel; Borodin, Oleg; Toney, Michael F. (Energy & Environmental Science)
Combined experimental and theoretical insights into electrolyte–electrode interfaces relevant to lithium ion batteries.

Surface structure evolution in a homologous series of ionic liquids - Haddad, Julia; Pontoni, Diego; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Steinrück, Hans-Georg; Reichert, Harald; Ocko, Benjamin M.; Deutsch, Moshe (Proceedings of the National Academy of Sciences)
Interfaces of room temperature ionic liquids (RTILs) are important for both applications and basic science and are therefore intensely studied. However, the evolution of their interface structure with the cation’s alkyl chain length n from Coulomb to van der Waals interaction domination has not yet been studied for even a single broad homologous RTIL series. We present here such a study of the liquid–air interface for n=2to 22 , using angstrom-resolution X-ray methods. For n<6 , a typical “simple liquid” monotonic surface-normal electron density profile ρe(z) is obtained, like those of water and organic solvents. For n>6 , increasingly more pronounced nanoscale self-segregation of the molecules’ charged moieties and apolar chains yields surface layering with alternating regions of headgroups and chains. The layering decays into the bulk over a few, to a few tens, of nanometers. The layering periods and decay lengths, their linear n dependence, and slopes are discussed within two models, one with partial-chain interdigitation and the other with liquid-like chains. No surface-parallel long-range order is found within the surface layer. For n=22 , a different surface phase is observed above melting. Our results also impact general liquid-phase issues like supramolecular self-aggregation and bulk–surface structure relations.

Effect of Structure and Disorder on the Charge Transport in Defined Self-Assembled Monolayers of Organic Semiconductors - Schmaltz, Thomas; Gothe, Bastian; Krause, Andreas; Leitherer, Susanne; Steinrück, Hans-Georg; Thoss, Michael; Clark, Timothy; Halik, Marcus (ACS Nano)

The Atomic Scale Electrochemical Lithiation and Delithiation Process of Silicon - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Toney, Michael F. (Advanced Materials Interfaces)

Memory Effect of Self-Assembled PS-b-PEO Block Copolymer Films with Selectively Embedded Functionalized TiO2 Nanoparticles - Kirschner, Johannes; Will, Johannes; Rejek, Tobias J.; Portilla, Luis; Berlinghof, Marvin; Schweizer, Peter; Spiecker, Erdmann; Steinrück, Hans-Georg; Unruh, Tobias; Halik, Marcus (Advanced Materials Interfaces)

Noble metal free photocatalytic H2 generation on black TiO2: On the influence of crystal facets vs. crystal damage - Liu, Ning; Steinrück, Hans-Georg; Osvet, Andres; Yang, Yuyun; Schmuki, Patrik (Applied Physics Letters)

Nanoscale Structure of the Oil-Water Interface - Fukuto, M.; Ocko, B. M.; Bonthuis, D. J.; Netz, R. R.; Steinrück, Hans-Georg; Pontoni, D.; Kuzmenko, I.; Haddad, J.; Deutsch, M. (Physical Review Letters)

In Situ Study of Silicon Electrode Lithiation with X-ray Reflectivity - Cao, Chuntian; Steinrück, Hans-Georg; Shyam, Badri; Stone, Kevin H.; Toney, Michael F. (Nano Letters)

Structure of n-Alkyltrichlorosilane Monolayers on Si(100)/SiO2 - Steinrück, Hans-Georg; Will, J.; Magerl, A.; Ocko, B. M. (Langmuir)

Order and Melting in Self-Assembled Alkanol Monolayers on Amorphous SiO2 - Haddad, Julia; Steinrück, Hans-Georg; Hlaing, Htay; Kewalramani, Sumit; Pontoni, Diego; Reichert, Harald; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Magerl, Andreas; Deutsch, Moshe; et al. (The Journal of Physical Chemistry C)

Structural Investigations of Self-Assembled Monolayers for Organic Electronics: Results from X-ray Reflectivity - Khassanov, Artoem; Steinrück, Hans-Georg; Schmaltz, Thomas; Magerl, Andreas; Halik, Marcus (Accounts of Chemical Research)

In situ investigation of two-step nucleation and growth of CdS nanoparticles from solution - Schiener, A.; Magerl, A.; Krach, A.; Seifert, S.; Steinrück, Hans-Georg; Zagorac, J.; Zahn, D.; Weihrich, R. (Nanoscale)

Nanoscale Structure of Si/SiO2/Organics Interfaces - Steinrück, Hans-Georg; Schiener, Andreas; Schindler, Torben; Will, Johannes; Magerl, Andreas; Konovalov, Oleg; Li Destri, Giovanni; Seeck, Oliver H.; Mezger, Markus; Haddad, Julia; Deutsch, Moshe; Checco, Antonio; et al. (ACS Nano)

Interface Engineering of Molecular Charge Storage Dielectric Layers for Organic Thin-Film Memory Transistors - Khassanov, Artoem; Schmaltz, Thomas; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Advanced Materials Interfaces)

Tuning the molecular order of C60-based self-assembled monolayers in field-effect transistors - Schmaltz, Thomas; Khassanov, Artoem; Steinrück, Hans-Georg; Magerl, Andreas; Hirsch, Andreas; Halik, Marcus (Nanoscale)

Pseudorotational Epitaxy of Self-Assembled Octadecyltrichlorosilane Monolayers on Sapphire (0001) - Steinrück, Hans-Georg; Magerl, A.; Deutsch, M.; Ocko, B. M. (Physical Review Letters)

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artoem; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Georg; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (ACS Nano)

Low-Voltage Self-Assembled Monolayer Field-Effect Transistors on Flexible Substrates - Schmaltz, Thomas; Amin, Atefeh Y.; Khassanov, Artoem; Meyer-Friedrichsen, Timo; Steinrück, Hans-Georg; Magerl, Andreas; Segura, Juan José; Voitchovsky, Kislon; Stellacci, Francesco; Halik, Marcus (Advanced Materials)

Oxygen diffusivity in silicon derived from dynamical X-ray diffraction - Will, J.; Gröschel, A.; Kot, D.; Schubert, M. A.; Bergmann, C.; Steinrück, Hans-Georg; Kissinger, G.; Magerl, A. (Journal of Applied Physics)